Chronic administration of proanthocyanidins or docosahexaenoic acid reverses the increase of miR-33a and miR-122 in dyslipidemic obese rats. - Laura Baselga-Escudero (Public Library of Science (PLoS), 2013)
miR-33 and miR-122 are major regulators of lipid metabolism in the liver, and their deregulation has been linked to the development of metabolic diseases such as obesity and metabolic syndrome. However, the biological importance of these miRNAs has been defined using genetic models. The aim of this study was to evaluate whether the levels of miR-122 and miR-33a in rat liver correlate with lipemia in nutritional models. For this purpose, we analyzed the levels of miRNA-33a and miR-122 in the livers of dyslipidemic cafeteria diet-fed rats and of cafeteria diet-fed rats supplemented with proanthocyanidins and/or ω-3 PUFAs because these two dietary components are well-known to counteract dyslipidemia. The results showed that the dyslipidemia induced in rats that were fed a cafeteria diet resulted in the upregulation of miR-33a and miR-122 in the liver, whereas the presence of proanthocyanidins and/or ω-3 PUFAs counteracted the increase of these two miRNAs. However, srebp2, the host gene of miR-33a, was significantly repressed by ω-3 PUFAs but not by proanthocyanidins. Liver mRNA levels of the miR-122 and miR-33a target genes, fas and pparβ/δ, cpt1a and abca1, respectively, were consistent with the expression of these two miRNAs under each condition. Moreover, the miR-33a and abca1 levels were also analyzed in PBMCs. Interestingly, the miR-33a levels evaluated in PBMCs under each condition were similar to the liver levels but enhanced. This demonstrates that miR-33a is expressed in PBMCs and that these cells can be used as a non-invasive way to reflect the expression of this miRNA in the liver. These findings cast new light on the regulation of miR-33a and miR-122 in a dyslipidemic model of obese rats and the way these miRNAs are modulated by dietary components in the liver and in PBMCs.